Effect of Trapezoidal-Shaped Well on Efficiency Droop in InGaN-Based Double-Heterostructure Light-Emitting Diodes - Ray-Ming Lin; Mu-Jen Lai; Liann-Be Chang; Chou-Hsiung Huang; Chang-Ho Chen (International Journal of Photoenergy)
We investigated the effects of different well shapes on the external quantum efficiency (EQE) and the efficiency droop in wide-well InGaN/GaN double-heterostructure light-emitting diodes. For forward current densities in the measurement range of greater than 135 A/cm2, the device featuring a trapezoidal well exhibited improved EQEs and alleviative efficiency droop, relative to those of the device featuring a rectangular well. The decreased Auger loss has been proposed as the main reason for the greater maximum efficiency that occurred at high current density (>50 A/cm2). For the devices incorporating trapezoidal and rectangular wells, the EQEs at 200 A/cm2 decreased by 14 and 40%, respectively, from their maximum values, resulting in the EQE at a current density of 200 A/cm2 of the device featuring a trapezoidal well being 17.5% greater than that featuring a rectangular well. These results suggest that, in addition to the decreased Auger loss, the alleviation in efficiency droop at higher current densities might be due to higher internal quantum efficiency resulted from the improved carrier injection efficiency of the trapezoidal well.